Local Wisdom and Cultural Nationalism in National Holiday Ceremonies: A Phenomenological Study in Islamic Education - Setiawan Budi; Muhammad Ibda’u Shulhi; Pribanus Wantara; Sholikhah, Nudialis (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study examines the integration of local wisdom in the commemoration of National Holidays within an Islamic educational setting, with particular attention to cultural performances conducted as part of ceremonial activities. Employing a descriptive qualitative method with a phenomenological approach, the research explores how performances such as colossal dramas, traditional dances, traditional costume parades, and the presentation of national and regional songs function as media for expressing local wisdom and national values. The findings indicate that these cultural performances embody key values including love of the homeland, cultural preservation, tolerance, religious moderation, and the spirit of mutual cooperation. Importantly, the forms of local wisdom displayed do not contradict Islamic teachings; rather, they align with Qur’anic principles of human diversity and mutual recognition as articulated in QS. Al-Hujurat (49:13). Beyond their ceremonial function, these activities play a significant role in socializing local wisdom and fostering national consciousness among students. Moreover, the integration of cultural expressions within national ceremonies serves as an effective form of cultural da’wah, enabling the internalization of religious and national values through contextual and experiential practices. This study contributes to discussions on cultural nationalism by highlighting the strategic role of ceremonial arts and cultural activities in integrating religious values and national identity within formal state rituals.